Comparison of Safety and Efficiency of General, Spinal and Epidural Anesthesia Methods Used for the Endoscopic Surgical Treatment of Ureteral Stones: Which One is Better To Access The Ureter and Reach The Stone? - Oztekin, Unal; Caniklioglu, Mehmet; Atac, Fatih; Kantekin, Cigdem Unal; Gurel, Abdullah; Isikay, Levent (Urology Journal, 2020)
Purpose: The aim of this study is to evaluate the effects of anesthesia methods on the success of urethral access and stone access achievement in endoscopic treatment of urolithiasis. Materials and Methods: In this prospective randomized study, 105 patients who underwent primary ureterorenoscopy (URS) procedure for ureteral stones were evaluated. The patients were randomized into three groups by permuted block randomization according to the applied anesthesia method: General anesthesia (GA): 33 patients, Spinal anesthesia (SA): 31 patients, and Epidural anesthesia (EA): 31 patients. Ten patients, whose ureteral access was not successful, were dropped out. The success of the three anesthesia methods on the success of the ureter access and its effects on surgical outcomes were compared. Results: There was no statistically significant difference among the three groups in terms of the demographic values and preoperative features except the American Society of Anesthesiologists (ASA) status. Dilatation and the access time to stone were statistically significantly longer in SA and EA group compared to the GA group. There was no statistically significant difference among the groups in terms of operation, lithotripsy time, stone-free rate (SFR), and complication rates. The Visual Analog Scale (VAS) scores in the 8th and 24th hours were statistically significantly higher in the GA group. Conclusion: In patients who decided to undergo primary ureterorenoscopy procedure, it can be suggested to treat with GA to provide a better relaxation of the ureter if there are no contraindications.